'La lampada ardente e risplendente': I diversi punti di vista su Giovanni Battista e il suo ruolo per il lettore all'interno del racconto giovanneo - Bianchini, Francesco (Biblica, 2024)
In narrative studies on the figure of the Baptist in the Gospel of John, a lack of attention to the different point of views regarding him is noticeable, but, more importantly, there is an absence of reflection on the pragmatic dimension of the character. Our contribution focuses on these two aspects. We examine each of the references to the Baptist in John (1,6-8; 1,15; 1,19-37; 3,23-4,1; 5,33-36; 10,40-42), paying attention to the different focalizations on him and how his character speaks to the reader. Additionally, we also consider the absence of any account of the Baptist’s death, unlike in the Synoptics, which leaves the narrative open. As a result of these analyses, we demonstrate that in the Fourth Gospel the character of the Baptist is presented as a prophetic voice that invites the reader to accept Jesus, the Son of God, and to grow in faith in him, but also as a paradigmatic witness who encourages a mission of courageous proclamation of Christ outside the community, with the aim of leading people to believe in him.